MEDIATING ROLE OF BRAND IMAGE IN THE EFFECT OF EWOM ON PURCHASE INTENTION OF ONLINE TICKETING APPS - Yuszana, Alfa; Tunjungsari, Hetty Karunia (International Journal of Application on Economics and Business, 2024)
This research aims to analyze the impact of Electronic Word of Mouth (EWOM) on the brand image perception of the Tiket.com application, understand how this brand image perception influences the purchase intention of Tiket.com application users, identify the direct impact of EWOM on the purchase intention of Tiket.com application users, and assess the indirect impact of EWOM on purchase intention through brand image as a mediating variable for Tiket.com application users. The research sample consisted of 203 respondents aged 18 and above, residing in the Greater Jakarta area, and having used the Tiket.com service at least twice in the last year. Respondent data were collected through an online questionnaire using Google Forms with non-probability sampling and purposive sampling techniques. Data analysis was performed using PLS-SEM with SmartPLS v3.2.9 software. The results of the study indicate that EWOM has a positive and significant impact on the brand image perception of the Tiket.com application. Brand image perception has a positive and significant impact on the purchase intention of Tiket.com application users. EWOM also has a positive and significant impact on the purchase intention of Tiket.com application users, and EWOM has a positive indirect impact on purchase intention through the brand image of the Tiket.com application.